The prevalence and characteristics of cow's milk protein allergy in infants and young children with iron deficiency anemia - Fu-Ping Lai; Yao-Jong Yang (Pediatrics and Neonatology)
Background: The clinical presentation of cow's milk protein allergy (CMPA) in children varies. This retrospective study aimed to investigate the prevalence and clinical manifestations of CMPA in young children who visited for evaluation of iron deficiency anemia (IDA). Methods: Patients aged <4 years who were diagnosed as having IDA (serum ferritin <12 ng/mL) at the National Cheng Kung University Hospital, Taiwan in the period 2005–2015 were reviewed. Their clinical presentations, laboratory data, endoscopy findings, and prognosis were analyzed. Results: Seven of 51 IDA patients (13.7%) had CMPA. The pallor (100%), failure to thrive (43%), and general edema (43%) were the common features. Six (86%) had hypoalbuminemia and four (57%) had positive occult blood in the stool. Of the five patients who underwent skin prick test, four (80%) had positive results. Most of the colonoscopies revealed erosive and hemorrhagic colitis and lymphoid hyperplasia, but none of the biopsies demonstrated eosinophilia in the lamina propria. All of the patients recovered from their IDA within seven months of cow's milk protein elimination and iron supplementation. Conclusion: CMPA should be considered in young children with undetermined IDA. Cow's milk protein elimination and iron supplementation help in the recovery.